1983
DOI: 10.1017/s0021932000014644
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to assessing the effect of birth order on the outcome of pregnancy

Abstract: SummaryA new approach is suggested for assessing the relationship between birth order and pregnancy risk. Population data are used to estimate the risk of a poor pregnancy outcome after different reproductive histories. The risk of a poor outcome at the first pregnancy appears to be twice that at subsequent pregnancies, but no change in risk is observed between the second and fifth birth orders. If there has been a previous poor pregnancy outcome, the risk of another is increased four-fold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…Primiparous mothers exhibited a higher risk of stillbirth than multiparous mothers. This finding is consistent with the risk pattern observed in both prospective and retrospective studies (Bakketeig & Hofman, 1989;Leridon, 1976;Roman et al, 1978;Yudkin & Baras, 1983).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Primiparous mothers exhibited a higher risk of stillbirth than multiparous mothers. This finding is consistent with the risk pattern observed in both prospective and retrospective studies (Bakketeig & Hofman, 1989;Leridon, 1976;Roman et al, 1978;Yudkin & Baras, 1983).…”
Section: Discussionsupporting
confidence: 91%
“…Genetically defective fetuses are also found more frequently among older mothers (Carr, 1971;James, 1970;Resseguie, 1974). This study showed that previous fetal wastage is associated with an increased risk of spontaneous miscarriage (Roman et al, 1978;Yudkin & Baras, 1983) and even one previous fetal loss increased the risk of stillbirth (cf. Swenson & Harper, 1979).…”
Section: Discussionmentioning
confidence: 87%
“…28 It is also possible that long intervals are selective of women in poorer health, who take longer to conceive 29 or that women who have long intervals did not want to become pregnant again and do not take as good care of themselves during pregnancy. 12 In addition, long IPIs are more likely for older women; older maternal age is associated with its own independent adverse effects on pregnancy outcomes, 30 though we see an effect even when we control for maternal age.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%
“…Bakketeig and Hoffman 14 modelled the prevalence of preterm births stratified by parity cohorts based on the women's ultimate family size to demonstrate that preterm birth did not increase with parity, but abortions were not included. Yudkin and Baras 15 published a study investigating the sequential effect of preceding birth outcomes by stratifying their data by parity. Carr‐Hill and Hall 6 looked at permutations of sequences of abortions, preterm and term livebirths and showed that compared with women who had had no prior preterm births, the percentage of preterm births after a previous preterm birth was tripled and increased sixfold after two previous preterm births with or without a preceding abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier attempts to model the effect of the sequence of prior pregnancy outcomes (i.e. combinations of births and abortions) 6,13–17 had limited data and were undertaken prior to the availability of sophisticated statistical software. None has investigated the complex sequence of all prior pregnancies.…”
Section: Introductionmentioning
confidence: 99%